Sosialisasi Pengolahan Sampah Anorganik Menjadi Eco Brick (Keranggan, Setu, Tangerang) - Marchelia Gupita Sari; Nurul Lestari Hasanuddin; Abdullah Hibrawan (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Eco-brick is an environmentally friendly brick management technique for plastic waste made from used PET plastic bottles in which various plastic bins have been filled to the brim, then compacted until it becomes hard to reach a certain amount of weight. Eco-brick can be one of the alternative affordable architectural material. The method conducted the implementation of Community Service activities is the socialization and presentation on eco-bricks assembly to the people of Kelurahan Keranggan, Setu, Tangerang, who face the issue of organic waste. Through socialization with presentations to the community, it is expected that it can increase the community participation in sustainable waste management. The results of Community Service activities are the increase in the level of community awareness in organic and organic waste management, as well as community better understanding of environmentally friendly alternative building materials from eco-brick.